Exudative Eroded Lesion and Fever - Aristóteles Rosmaninho; Sandrina Carvalho (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
A 4 month year-old boy presented with a 5 day history of an erythematous exudative lesion on the lateral aspect of the face, neck and thorax. He had been observed by his physician and a topical fusidic acid ointment had been applied without success. His prior medical history was remarkable for an atopic dermatitis. On physical examination the patient had fever of 38.6ºC. An exudative erythematous lesion with multiple grouped peripheral umbilicated vesiculopustules and punched-out ulcers were observed on the face, neck and thorax (Figure 1). He hadn´t received vaccination in the prior 2 months. The laboratory showed no abnormalities except for an erythrocyte sedimentation rate of 19 mm/hr. A Tzanck test showed acantholytic balloon cells. A diagnosis of eczema herpeticum was made.